Effectiveness of Dayah Jabal Nur Policy in Improving Students' Achievement Motivation - Moch Rizal Al-Faqi; Said Alwi; Sofyan Arianto (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study explores the effectiveness of educational policies implemented at Dayah Jabal Nur in enhancing students’ achievement motivation. While previous research has highlighted the importance of leadership and values in Islamic boarding schools (dayah), few have specifically examined the institutional policies and their influence on students' academic and non-academic performance. Employing a qualitative approach with a phenomenological method, this research aims to understand how policy implementation at Dayah Jabal Nur fosters both intrinsic and extrinsic motivation among santri (students). Data were collected through in-depth interviews, participant observation, and document analysis involving teachers, students, and administrators. The findings indicate that the educational policies—such as reward systems, extracurricular activities, and character development programs—contribute significantly to increasing student motivation. However, challenges remain, particularly in aligning students' understanding of the policy goals and ensuring consistent commitment from all stakeholders. The study concludes that well-structured and participatory educational policies play a crucial role in shaping a competitive and spiritually grounded learning environment within Islamic boarding schools